Deteksi Dini Krisis Lewat Profit And Loss Sharing (PLS) - Khairul Umam Khudhori; Loni Hendri (Al-Intaj, 2020)
Financial crisis is a danger that always haunts financial stability of every country. Islamic finance as the new comer also gets into this trouble. Fortunately, Islamic finance system is stronger than conventional facing the crisis. This strong may come from its principles that support it. This paper uses a library research to examine the PLS system and it benefits to financial stability. The finds of this paper are Islamic financial system is more stable than conventional one, and  PLS system can be used as the early warning of financial crisis.